Role of the private sector in Caribbean development - Thompson, P. A. ([CAIC] BridgetownBB, 1987)
Defines the concept of economic transformation and contends that one of its essential requirements is genuine political democracy. Reviews the historical origins of the private sector in CARICOM countries and points out the need for the public and private sectors and the Caribbean trade union movement to work together on aspects of economic planning, implementation and evaluation. Discusses the class struggle and economic transformation and notes that ideological extremes should be avoided in the search for solutions. Outlines four initiatives involving public and private sector cooperation currently in train or planned in CARICOM countries.